Intraspecific Morphometric Variation in a New Species of Ceratomyxa Thélohan 1892 (Cnidaria) from the South Atlantic Ocean: An Ecomorphological Study Using Geometric Morphometrics - Delfina M. P. Cantatore; Martina Lisnerová; Paula S. Marcotegui; María A. Rossin; Astrid S. Holzer (Biology)
A new species of Ceratomyxa (Ceratomyxidae, Myxosporea) was found infecting the gall bladder of the Argentine croaker Umbrina canosai Berg 1895 (Sciaenidae, Perciformes) from the Argentine sea. Using an integrative taxonomic approach that combines morphological, bioecological, and molecular analyses, we provide evidence that clearly differentiates this species from known taxa and formally describe Ceratomyxa fialai as a new species. This study is the first to apply landmark-based geometric morphometrics (GM) in myxozoan research, providing a detailed analysis of conspecific morphometric variation of ceratomyxid myxospores, examining their natural variation within and among different ceratomyxids infecting the gall bladder of U. canosai. Using GM analyses, we successfully capture and quantify phenotypic variation at the organismal level. Our results suggest that myxospore shape variation may be driven by both developmental noise and phenotypic plasticity. The work highlights the utility of GM in advancing the understanding of myxozoan morphology and its evolutionary implications and emphasizes the need for further research on myxospore shape evolution and its ecological and adaptive significance in natural populations.